Possibilities of action of a team of multiprofessional residents in mental health within a psychiatric hospital: experience report (Research, Society and Development, 2022)
Objective: To report the experience defined by a team of multiprofessional residents in a psychiatric hospital in the Federal District region. Method: This is a qualitative and descriptive study, of the experience report type, developed from the experiences of creation, planning and execution of interventions with patients hospitalized in the service, allocated in the emergency room (ER) and ward (ALA). The methodological course of the Arch method by Charles Maguerez was followed. Results: In this extension experience, 5 interventions were produced, through therapeutic workshops, aimed at the psychosocial rehabilitation of the participants. Conclusion: The actions constructed and developed through the interventions have become important teaching and learning possibilities for multidisciplinary mental health residents, reverberating the development of important characteristics for professional team practice. The strategies used in the interventions provided an awareness of the possibilities of action and care in mental health with patients in psychological distress, within a service, traditionally an asylum.